THE EFFECT OF PRICING, TASTE, AND SERVICE QUALITY ON CUSTOMER SATISFACTION: CASE STUDY OF RESTAURANT BUNDER LAB BOGOR - Muniroh, Leny; Andriyansah; Kuraesin, Ecin (Universitas Ibn Khaldun Bogor, 2024)
This study aims to determine how the effect of Pricing, Taste, and Service Quality on Consumer Satisfaction of Resto Bunder Lab. The research method used in this research is a quantitative approach. This data collection technique is carried out using several methods such as: Library method by collecting data using several books and journals, survey method through distributing questionnaires, interview method with respondents or research subjects directly, and online method data obtained from several websites, social media, or other platforms